BRI1 controls vascular cell fate in the Arabidopsis root through RLP44 and phytosulfokine signaling - Holzwart, Eleonore; Garnelo Gómez, Borja; Augustin, Sebastian; Askani, Jana Christin; Schürholz, Anne-Kathrin; Wolf, Sebastian (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Multicellularity arose independently in plants and animals, but invariably requires a robust determination and maintenance of cell fate that is adaptive to the environment. This is exemplified by the highly specialized water- and nutrient-conducting cells of the plant vasculature, the organization of which is already prepatterned close to the stem-cell niche, but can be modified according to extrinsic cues. Here, we show that the hormone receptor BRASSINOSTEROID INSENSITIVE 1 (BRI1) is required for root vascular cell-fate maintenance, as BRI1 mutants show ectopic xylem in procambial position. However, this phenotype seems unrelated to canonical brassinosteroid signaling outputs. Instead, BRI1 is required for the expression and function of its interacting partner RECEPTOR-LIKE PROTEIN 44 (RLP44), which, in turn, associates with the receptor for the peptide hormone phytosulfokine (PSK). We show that PSK signaling is required for the maintenance of procambial cell identity and quantitatively controlled by RLP44, which promotes complex formation between the PSK receptor and its coreceptor. Mimicking the loss of RLP44, PSK-related mutants show ectopic xylem in the position of the procambium, whereas rlp44 is rescued by exogenous PSK. Based on these findings, we propose that RLP44 controls cell fate by connecting BRI1 and PSK signaling, providing a mechanistic framework for the dynamic balancing of signaling mediated by the plethora of plant receptor-like kinases at the plasma membrane.